2013
DOI: 10.1007/s10903-013-9873-x
|View full text |Cite
|
Sign up to set email alerts
|

“When you walk in the rain, you get wet”: A Qualitative Study of Ghanaian Immigrants’ Perspective on the Epidemiological Paradox

Abstract: This study sought to understand the perceptions of Ghanaian immigrants of the health status and health trajectory of their community. We conducted focus groups and interviews with 63 primarily Ghanaian immigrants living in New York City. Nearly all participants observed that Ghanaians are generally healthy when they arrive in the US, but that their health declines over time. Participants identified four causes of this perceived deterioration: changes in health behaviors, increased stress, environmental exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 23 publications
0
52
1
Order By: Relevance
“…Cultural perspectives of diseases and illness determine healthcare behaviors, which in turn shape healthcare experiences. Eight articles discussed the impact of culture on the healthcare experiences of African immigrants in the U.S. [11,61,68,69,[71][72][73][74]. In African immigrant communities, for example, diseases such as HIV and cancer are viewed as the result of spiritual issues?…”
Section: Cultural Influence Traditional Beliefsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cultural perspectives of diseases and illness determine healthcare behaviors, which in turn shape healthcare experiences. Eight articles discussed the impact of culture on the healthcare experiences of African immigrants in the U.S. [11,61,68,69,[71][72][73][74]. In African immigrant communities, for example, diseases such as HIV and cancer are viewed as the result of spiritual issues?…”
Section: Cultural Influence Traditional Beliefsmentioning
confidence: 99%
“…Therefore, it is not uncommon for many African immigrants to consult oracles and traditional healers in their home countries, regarding those types of health problems [72,73]. The study by Kaplan et al, showed it was common for participants to delay office visits until the diseases or illnesses were certifiably irreversible or severe enough to halt daily activities [68]. Results from another study showed HIV-positive African immigrant women sought treatment when the condition was already in its late stage [74].…”
Section: Cultural Influence Traditional Beliefsmentioning
confidence: 99%
See 3 more Smart Citations